A birth cohort analysis of the smoking epidemic in West Germany. Issue 1 (February 1993) - Brenner, H
Abstract : STUDY OBJECTIVE--The aim was to provide insights in the spread of the smoking epidemic and eventual progress against cigarette smoking in West Germany. DESIGN--This was a retrospective birth cohort analysis based on a cross sectional national survey. SETTING--The survey was conducted in 1987 by the Ministry of Youth, Family and Health in order to identify priorities for health policy and promotion. The target population were all residents of German nationality above the age of 14 years. STUDY POPULATION--1721 men and women of the birth cohorts 1911-20, 1921-30, 1931-40, 1941-50, 1951-60, and 1961-70 were included in this analysis (65.7% overall response rate). MEASUREMENTS AND MAIN RESULTS--The participants were asked for their detailed life time history of cigarette smoking in a personal interview. This information was used to calculate and plot historical smoker prevalences by sex, level of school education, birth cohort, and calendar year after correcting for differential survival of smokers and non-smokers. In men, smoking prevalences increased slowly from birth cohort to birth cohort and reached a maximum of more than 70% in the 1941-50 cohort in the early 1970s. While smoker prevalences were considerably lower in the two youngest birth cohorts among better educated men, no major changes were observed in men with lower educational status. The rise of the smoking epidemic in women seems to have levelled off only very recently. CONCLUSIONS--In contrast to other countries with more powerful antismoking campaigns, no major progress in the fight against cigarette smoking has so far been made in West Germany. Major public health efforts are badly needed to limit the epidemic of smoking attributable diseases in this country.